(untitled) - Hudson, Jydy A. (Teton NewMedia, 2003)
CD-ROM FEATURES: 104 additional images. The Figure Index is presented alphabetically and allows users to selectively search by disease, disorder or by anatomic features. Elaborate search capabilities allow users instantaneous access to their selections. PDF formal presentation allows for easy navigation and for easy printing. Hyperlinked figures within the pdf content for easy linking to figures in other sections. Toll-Free Technical support when you register.
Keywords: Abdomen,Acute abdomen,Abdomen; Radiography,Diagnosis,Anatomy and histology